2021
DOI: 10.1177/07334648211048189
|View full text |Cite
|
Sign up to set email alerts
|

Older Lesbian, Gay, Bisexual, Transgender, and Queer Adults’ Experiences With Discrimination and Impacts on Expectations for Long-Term Care: Results of a Survey in the Southern United States

Abstract: The number of older adults in the United States is projected to increase in coming years, including the number of lesbian, gay, bisexual, transgender, queer, or questioning (LGBTQ+) older adults requiring long-term care (LTC) services. We conducted an online survey of older LGBTQ+ adults living in the Southern United States between January and March of 2018 to inquire about their anticipation of discrimination in and willingness to utilize LTC services. We found that 78.6% of respondents ( N = 789) anticipated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Many of the older Black lesbians in this study acknowledged their needs and plans for moving to a LTC facility, their expectation of the facility environment, and their desire to create alternative communities of mutual support. The findings from this study contribute to the scant literature about the aging experiences of Black lesbians [ 9 , 11 , 12 , 14 , 20 ] and demonstrate parallel sentiments around aging and LTC use for the larger, SGM older adult population [ 17 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Many of the older Black lesbians in this study acknowledged their needs and plans for moving to a LTC facility, their expectation of the facility environment, and their desire to create alternative communities of mutual support. The findings from this study contribute to the scant literature about the aging experiences of Black lesbians [ 9 , 11 , 12 , 14 , 20 ] and demonstrate parallel sentiments around aging and LTC use for the larger, SGM older adult population [ 17 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 52%
“…The environment in which care is provided and received is a major concern for those in the SGM community. Many older SGM adults have valid concerns that revolve around threats of discrimination and mistreatment when considering moving to long-term care facility [ 17 , 18 ]. These same sentiments were expressed by several participants when asked if they have considered moving to a LTC facility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite legal advances to protect LGBT+ people from healthcare discrimination in many countries, 2 experience and anticipation of discrimination within healthcare continue to be concerns, which can delay seeking health services. [3][4][5][6][7][8][9][10][11] The acronym LGBT+ refers to lesbian, gay, bisexual and/or transgender people, and anyone who considers themselves to have a minority sexual orientation, gender identity or gender history (the relationship between gender identity and sex assignedat birth). Experience of discrimination among LGBT+ people is linked to higher incidence of serious illness (eg, cancer, cardiovascular disease and respiratory disease), 12 poorer health outcomes, [13][14][15][16] more risky health behaviours (eg, alcohol and tobacco consumption) and difficulties accessing healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Data from 27 countries revealed that 8% of adults have a minority sexual orientation, and 1% identify as trans or non-binary 1. Despite legal advances to protect LGBT+ people from healthcare discrimination in many countries,2 experience and anticipation of discrimination within healthcare continue to be concerns, which can delay seeking health services 3–11. The acronym LGBT+ refers to lesbian, gay, bisexual and/or transgender people, and anyone who considers themselves to have a minority sexual orientation, gender identity or gender history (the relationship between gender identity and sex assignedat birth).…”
Section: Introductionmentioning
confidence: 99%